2021
DOI: 10.1123/ijspp.2019-0974
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Force Development, Muscle Architecture, and Performance in Elite Weightlifters

Abstract: Purpose: The purpose of the present study was to investigate the relationship between weightlifting performance and the rate of force development (RFD), muscle architecture, and body composition in elite Olympic weightlifters. Methods: Six male Olympic weightlifters (age 23.3 [3.4] y, body mass 88.7 [10.2] kg, body height 1.76 [0.07] m, snatch 146.7 [15.4] kg, clean and jerk 179.4 [22.1] kg), all members of the national team, participated in the study. Athletes completed a 16-week periodized training program a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 20 publications
6
42
0
Order By: Relevance
“…However, a recent study in 12 well-trained track and field throwers (4 hammer throwers with performance range from 65.04 to 73.23 m, 4 javelin throwers with performance range from 64.91 to 79.72 m, 3 discus throwers with performance range from 50.55 to 55.84 m and 1 shot putter with performance of 15.52 m) showed that vastus lateralis muscle thickness and fascicle angle remained unaltered following 25 weeks of training, while fascicle length increased significantly [ 46 ]. Although changes in vastus lateralis fascicle angle were similar to previous studies, muscle thickness was higher compared to studies in collegiate (2.66–2.78 cm) [ 19 ] and young throwers (2.57–2.71 cm) [ 41 , 45 ], but similar with a recent study with elite weightlifters (2.97 ± 0.28 cm) [ 79 ]. In addition, a study in well-trained track and field throwers found similar results in vastus lateralis muscle thickness (3.0 ± 0.5 cm) [ 43 ].…”
Section: Muscle Architecture Characteristicssupporting
confidence: 88%
“…However, a recent study in 12 well-trained track and field throwers (4 hammer throwers with performance range from 65.04 to 73.23 m, 4 javelin throwers with performance range from 64.91 to 79.72 m, 3 discus throwers with performance range from 50.55 to 55.84 m and 1 shot putter with performance of 15.52 m) showed that vastus lateralis muscle thickness and fascicle angle remained unaltered following 25 weeks of training, while fascicle length increased significantly [ 46 ]. Although changes in vastus lateralis fascicle angle were similar to previous studies, muscle thickness was higher compared to studies in collegiate (2.66–2.78 cm) [ 19 ] and young throwers (2.57–2.71 cm) [ 41 , 45 ], but similar with a recent study with elite weightlifters (2.97 ± 0.28 cm) [ 79 ]. In addition, a study in well-trained track and field throwers found similar results in vastus lateralis muscle thickness (3.0 ± 0.5 cm) [ 43 ].…”
Section: Muscle Architecture Characteristicssupporting
confidence: 88%
“…Then, participants seate on a custom-made steel leg press chair and placed both feet on a force platform (Applie Measurements Ltd. Co., Reading, UK; WP800, A/D sampling frequency 1 kHz), whic was positioned vertical to the laboratory wall. Knee angle was set at 120° and hip angle a 100° [25,36]. A real-time visual feedback of the force applied was provided for each effo via a computer monitor placed just above the force platform in front of the participant Two attempts were allowed with progressively increasing forces followed by two explo sive attempts with approximately 80% of the individual perceived maximum strength Subsequently, three maximum efforts were performed with 3 s duration and with 3 mi rest between them.…”
Section: Leg Press Isometric Peak Force and Rate Of Force Developmentmentioning
confidence: 99%
“…Then, participants seated on a custom-made steel leg press chair and placed both feet on a force platform (Applied Measurements Ltd. Co., Reading, UK; WP800, A/D sampling frequency 1 kHz), which was positioned vertical to the laboratory wall. Knee angle was set at 120 • and hip angle at 100 • [25,36]. A real-time visual feedback of the force applied was provided for each effort via a computer monitor placed just above the force platform in front of the participants.…”
Section: Leg Press Isometric Peak Force and Rate Of Force Developmentmentioning
confidence: 99%
“…However, greater pennation angles are also associated with slower contraction velocities and thus lower power production [ 7 , 8 , 15 ]. For example, in previous studies from our laboratory, no significant correlations were found between vastus lateralis fiber pennation angle and performance in power-demanding activities, like sprinting, throwing, and jumping [ 12 , 13 , 14 , 16 , 17 ]. Muscle fascicle length has also been linked with performance in power-demanding activities [ 16 , 17 , 18 , 19 , 20 , 21 ], as longer fascicles allow for faster contraction speeds, a larger range of movement, and shift rightward the torque/angle relationship [ 7 ].…”
Section: Introductionmentioning
confidence: 74%
“…Along this line, individuals with greater muscle thickness tend to have a higher maximum strength and power production compared to individuals with smaller muscle thickness, while training-induced changes in muscle thickness are linked to the concomitant increases of maximum strength and power performance [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Muscle fascicle pennation angle, e.g., the angle between muscle fascicles and aponeurosis or muscle line action [ 8 ], has also be linked with strength [ 12 , 13 , 14 ], while training-induced changes in pennation angle and maximum strength are closely linked [ 9 ], as this influences the mechanical efficiency of force transmission to the tendons/aponeuroses [ 8 , 15 ]. However, greater pennation angles are also associated with slower contraction velocities and thus lower power production [ 7 , 8 , 15 ].…”
Section: Introductionmentioning
confidence: 99%